Loyalitas atau ghuluw? Telaah fiqih terhadap fenomena fanatisme berlebihan terhadap organisasi islam di Indonesia - Pratama, Ivan Cahya (Maliki Interdisciplinary Journal, 2025)
In practicing their faith, Muslims often encounter challenges in balancing textual religious understanding with the realities of a diverse society. The emergence of ghuluw (religious extremism) and tafrith (neglect of religious obligations) indicates that some segments of the Muslim community have yet to fully implement the principle of tawazun (balance) as taught in Islamic jurisprudence (fiqh). This study aims to explore the concept of tawazun in fiqh as a normative solution to maintain harmony between group loyalty and the unity of the Muslim community. The method used is a literature review with a descriptive-qualitative approach, focusing on the works of both classical and contemporary scholars. The findings show that tawazun is a central principle in fiqh, promoting a moderate, just, and non-extremist approach to religious practice. Furthermore, tawazun offers a response to the fragmentation of thought within the Muslim community and serves as a foundation for fostering inclusive and tolerant religious life. By internalizing the values of tawazun, Muslims are expected to preserve Islamic brotherhood (ukhuwah Islamiyah) without compromising their group identity or the core principles of Islamic law.